1997
DOI: 10.5694/j.1326-5377.1997.tb140078.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and abdominal hysterectomy: a cost comparison

Abstract: Objective: To compare the cost of laparoscopically assisted vaginal hysterectomy (LAVH) with that of total abdominal hysterectomy (TAH) under casemix. Design: Retrospective comparison of the costs, operating time and length of hospital stay. Patients: The 16 women undergoing consecutive LAVH and 16 age‐matched women undergoing TAH between 1 February 1994 and 31 July 1995; all women were public patients undergoing hysterectomy for benign disease. Setting: Monash Medical Centre, a large tertiary teaching hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…A large difference of 3.55 days found in our data (table 1) was the main driver of cost savings. Studies from the USA, 21 Australia, 22 France 23 and the UK 24 found costs of TAH and TLH to be similar or not significantly different and consistently reported a significantly shorter hospital stay for TLH. A recent cost comparison of different treatment approaches for endometrial cancer found TLH to be the least expensive alternative with costs ranging from US$6581-US$10 128 compared to US$7009-US$12 847 for TAH, depending on the range of costs included in the analysis.…”
Section: Discussionmentioning
confidence: 97%
“…A large difference of 3.55 days found in our data (table 1) was the main driver of cost savings. Studies from the USA, 21 Australia, 22 France 23 and the UK 24 found costs of TAH and TLH to be similar or not significantly different and consistently reported a significantly shorter hospital stay for TLH. A recent cost comparison of different treatment approaches for endometrial cancer found TLH to be the least expensive alternative with costs ranging from US$6581-US$10 128 compared to US$7009-US$12 847 for TAH, depending on the range of costs included in the analysis.…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Tsaltas J et al, fibroid was the most common indication in TAH group as in this study but in NDVH group DUB was more common indication in Shanthini and all other studies. 18,22 In the present study, volume reductive methods were used in 15 cases. Mean blood loss LAVH was 150 ml but still it was less than mean blood loss in TAH (201 ml.)…”
Section: Discussionmentioning
confidence: 99%
“…This may provide financial/ economic benefits to the hospital because it allows higher patient occupancy per bed and advantages the patient by allowing resumption of daily activities earlier than conventional surgery. Davison et al (1993) and Tsaltas et al (1997) family disruptions; and an unnecessary financial expenditure on the health care system.…”
Section: (A) Cost Savings To Hospital and Patientmentioning
confidence: 97%